Strength Analysis of Typical Koepe Pulley Constructions Applied in Mine Hoisting Installations - WOLNY, Stanisław; ŁADECKI, Bogusław (Engineering Transactions, 2017)
A large number of hoisting installations equipped with Koepe pulleys are presently operating in Polish mines. In many instances, cracks of fatigue character occur in those Koepe pulley constructions. Conducting periodic repairs in the areas of crack formations only temporarily fixes this issue. In order to eliminate this problem, this study aims at identifying the sources of fatigue crack formation and growth in Koepe pulleys. With this objective, the numerical models of the Koepe pulley construction were developed and analysed using the finite element method (FEM). The FEM analysis was preceded by the dynamic analysis of the hoisting installation during its normal work cycle. The results of these analyses – dynamic and strength – were verified by experiments on the real object by measuring forces and stresses in the selected areas of the pulley wheel. The obtained results provided the grounds for assessing the fatigue life and for introducing an improvement to the design of the considered Koepe pulley constructions.